Uji Efektifitas Ekstrak Etanol Daun Jarak Pagar (Jatropha curcas L.) Terhadap Bakteri Staphylococcus epidermidis Dan Propionibacterium acnes Secara In Vitro - Alfi Sapitri; Prima Jaya Nazara; Vivi Asfianti (Herbal Medicine Journal, 2020)
Jatropha curcas L. leaves are known as one of the traditional medicinal ingredients. Jatropha leaves contain nutritious substances such as Alkaloids, Flavonoids, Tannins, and Saponins which have the ability as an antibacterial. Penelitian ini bertujuan untuk mengetahui efektifitas ekstrak etanol daun jarak pagar terhadap bakteri Stapphylococcus epidermidis dan Propionibacterium acnes secara in vitro. The method used in this study is experimental, including the collection and processing of Jatropha curcas (Jatropha curcas L.) samples, macroscopic and microcospic examinations, phytochemical screening, antibacterial effectiveness testing using diffusion method using disc paper, and using one-way analysis of data analysis methods. (One Way Anova). The results of ethanol extract of Jatropha leaves were able to inhibit bacterial growth ranging from concentrations of 110%, 125%, 250%, 300%, 350% and as a positive control using a tetracycline comparison. This research shows that the higher the concentration, the wider the inhibition zone formed.